2010
DOI: 10.1105/tpc.109.071779
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsis thaliana Myo-Inositol 1-Phosphate Synthase1 Gene Is Required forMyo-inositol Synthesis and Suppression of Cell Death

Abstract: L-myo-inositol 1-phosphate synthase (MIPS; EC 5.5.1.4) catalyzes the rate-limiting step in the synthesis of myo-inositol, a critical compound in the cell. Plants contain multiple MIPS genes, which encode highly similar enzymes. We characterized the expression patterns of the three MIPS genes in Arabidopsis thaliana and found that MIPS1 is expressed in most cell types and developmental stages, while MIPS2 and MIPS3 are mainly restricted to vascular or related tissues. MIPS1, but not MIPS2 or MIPS3, is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
225
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(246 citation statements)
references
References 82 publications
(111 reference statements)
15
225
3
Order By: Relevance
“…Four of those SNPs were included in the GWA mapping and were moderately associated (2log(P value)>4) with heat stress response in region C. The strongest associated SNP is responsible for a nonsynonymous change in the protein sequence of AT5G10170, which codes for MyoInositol 1-Phosphate Synthase3 (MIPS3). MIPS3 expression was most prominent in vascular tissue (Donahue et al, 2010), and heat-induced expression was reported during the seedling stage (Khurana et al, 2012). The Arabidopsis genome has three MIPS genes.…”
Section: A Possible Genetic Link Between Developmental Timing Of Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Four of those SNPs were included in the GWA mapping and were moderately associated (2log(P value)>4) with heat stress response in region C. The strongest associated SNP is responsible for a nonsynonymous change in the protein sequence of AT5G10170, which codes for MyoInositol 1-Phosphate Synthase3 (MIPS3). MIPS3 expression was most prominent in vascular tissue (Donahue et al, 2010), and heat-induced expression was reported during the seedling stage (Khurana et al, 2012). The Arabidopsis genome has three MIPS genes.…”
Section: A Possible Genetic Link Between Developmental Timing Of Flowmentioning
confidence: 99%
“…FRI-sf2 (CS6209) can also be obtained from the ABRC Stock Center. In addition, the following SALK T-DNA insertion mutants (Alonso et al, 2003) and GABI-Kat T-DNA insertion mutants (Kleinboelting et al, 2012) were obtained from NASC: qul2-2 (SALK_065604c), AT2G03505 (GABI_745A07), AT2G03490 (SALK_125910), mips3-2 (SALK_120131c; Donahue et al, 2010), and AT5G10200 (SALK_040912c). Seeds of the mutants qul1-1 and qul1-1 qul2-1 were kindly provided by L. Østergaard (Fuentes et al, 2010).…”
Section: Plant Materialsmentioning
confidence: 99%
“…Moreover, compared with wild type, all EMS mutant seeds are wrinkled and empty. Interestingly, similar phenotypes have been showed in Arabidopsis mips mutants (Donahue et al 2010) which show a significant percentage of wrinkled and empty seeds compared with their corresponding wild-type accessions. During wild-type embryogenesis (Fig.…”
Section: Differential Expression Of Pv_bat93 Mips Cdna In Wild-type Amentioning
confidence: 51%
“…, Pisum sativum (Imhoff and Bourdu 1973), Vigna radiata (Adhikari et al 1987;Wongkaew et al 2010), Oryza sativa (Hait et al 2002), Glycine max (Iqbal et al 2002), Citrus paradisi (Abu-abied and Holland 1994), Sesamum indicum (Chun et al 2003), Arabidopsis thaliana (Johnson 1994), Passiflora edulis (Abreau and Aragao 2007), and Phaseolus vulgaris (Wang and Johnson 1995). Although yeast and animal genomes contain a single gene encoding MIPS (GhoshDastidar et al 2006;Donahue et al 2010), plant have multiple MIPS genes (Torabinejads and Gillaspy 2006;Donahue et al 2010). In common bean, three sequences encoding MIPS gene have been reported: PvMIPSs (GenBank accession AJ853494), expressed mainly in developing seeds; PvMIPSr (GenBank accession U38920), expressed mainly in roots (Wang and Johnson 1995;Johnson and Wang 1996); and PvMIPSv (GenBank accession FN356964), expressed in vegetative organs, especially leaf tissues (Fileppi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation